138k views
5 votes
Solve the following system of equations by using the substitution method.

y= 6x - 11
-2x - 3y = -7

- (1,2)
- (2,1)
- (-3,1)
- (2,4)

User Zachleat
by
5.4k points

1 Answer

4 votes

Use the first equation (y= 6x - 11) to simplify the second equation (reduce the number of variables there from 2 to 1):


-2x - 3(6x - 11) = -7

-2x - 18x + 33 = -7. Combining like terms, -20x = -40, or x = 2.

If x = 2, use the first equation to determine y: y = 6(2) - 11 = 1

The solution is (2,1).

User Henrikmerlander
by
5.3k points